2013
DOI: 10.1073/pnas.1220353110
|View full text |Cite
|
Sign up to set email alerts
|

Lineage tracing reveals multipotent stem cells maintain human adenomas and the pattern of clonal expansion in tumor evolution

Abstract: The genetic and morphological development of colorectal cancer is a paradigm for tumorigenesis. However, the dynamics of clonal evolution underpinning carcinogenesis remain poorly understood. Here we identify multipotential stem cells within human colorectal adenomas and use methylation patterns of nonexpressed genes to characterize clonal evolution. Numerous individual crypts from six colonic adenomas and a hyperplastic polyp were microdissected and characterized for genetic lesions. Clones deficient in cytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 49 publications
8
77
0
4
Order By: Relevance
“…Numerous groups have isolated putative cancer stem cells from primary tumor specimens and demonstrated chemoresistance and self-renewal of this population, suggesting that these cells are present before chemotherapy is given. Lineage tracing experiments done in colonic adenomas support this hypothesis, demonstrating that stem cells exist in a quiescent state but stochastically expand in response to evolution or microenvironment stressors (13). Although some models have shown that “stemness” can be induced by stressors such as chemotherapy, it seems unlikely that full chemotherapy resistance is induced by administration of primary therapy, In other gynecologic malignancies, such as gestational trophoblastic disease and ovarian germ cell tumors, durable cures are frequently obtained with similarly aggressive and toxic chemotherapeutic regimens.…”
Section: Why Do Cancer Stem Cells In Ovarian Cancer Make Sense?mentioning
confidence: 96%
“…Numerous groups have isolated putative cancer stem cells from primary tumor specimens and demonstrated chemoresistance and self-renewal of this population, suggesting that these cells are present before chemotherapy is given. Lineage tracing experiments done in colonic adenomas support this hypothesis, demonstrating that stem cells exist in a quiescent state but stochastically expand in response to evolution or microenvironment stressors (13). Although some models have shown that “stemness” can be induced by stressors such as chemotherapy, it seems unlikely that full chemotherapy resistance is induced by administration of primary therapy, In other gynecologic malignancies, such as gestational trophoblastic disease and ovarian germ cell tumors, durable cures are frequently obtained with similarly aggressive and toxic chemotherapeutic regimens.…”
Section: Why Do Cancer Stem Cells In Ovarian Cancer Make Sense?mentioning
confidence: 96%
“…Genetic lineage tracing using inducible recombination has not yet been performed in human cancers; however, analysis of spontaneous mutations in mitochondrial DNA as well as of the methylation pattern of nonexpressed genes has allowed reconstruction of clonal lineages in normal colonic crypts and adenomas from human patients carrying familial adenomatous polyposis apc mutations (69,70). These studies show the existence of important tumor heterogeneity with rapidly growing clones, supporting the existence of quickly dividing CSCs that fuel tumor growth (69).…”
Section: Lineage Tracing and Clonal Dynamics Of Cancer Stem Cellsmentioning
confidence: 96%
“…Graham and colleagues used lineage-tracing techniques based on nuclear and mitochondrial DNA lesions in human colon adenomas to identify stem cell populations within adenoma crypts with multipotent potential and map their evolution over time. A punctuated model of rare clonal expansions interspersed with prolonged periods of stasis was suggested (Humphries et al, 2013). …”
Section: Gradualism Versus Punctuated Evolutionmentioning
confidence: 99%